Cost recovery evaluation of Al Ain construction and demolition waste treatment plant - Taher, Ibrahim Abdulmajid Ibrahim (2013)
Waste management is a major challenge facing the developing countries. The rapid urban growth and economic development in Abu Dhabi Emirate has resulted in extreme increase in the daily generation of waste quantity. The Government of Abu Dhabi has initiated several recycling projects toward balancing between the environmental sustainability along with the economic growth to ensure the long-term quality of life of its citizens. The aim of this dissertation is to evaluate the cost recovery of one of the recycling projects in Abu Dhabi Emirate, namely Al Ain crushing and demolition waste treatment plant. In light of the aim the objectives of this research are to explore the cost recovery scenarios for the plant under different policy and economy options, introduce the optimum solution in terms of cost recovery considering the environmental, social, and economic implications, and develop an integrated solution for the management of C&D waste projects in the Abu Dhabi Emirate. Developing a financial model and considering several assumptions for the relevant factors to determine the cost recovery scenarios of the project, the findings of this research indicate the negligence of clear cost recovery approach and lack of necessary legislations and financial solutions. The identified scenarios elaborated that the current situation will fail in achieving the return on investment during the course of the contract regardless of the adverse environmental and economic impacts of current practices. Moreover, the prevailing practices and activities of the construction industry indicates a real need of major governmental decrees to enhance the supervision and monitoring related activities, create stable market for the recycled materials through government-funded projects managed by public organizations, in addition to intensive awareness and education programs to promote environmentally sound practices. These set of political support, law enforcement, environment considering encouragement, will reform the construction industry toward achieving the waste sector strategy. Nevertheless, the research recommends developing the implementation of tipping fee mechanism as a substantial solution toward the successfulness of the recycling projects in Abu Dhabi.